Construction of PCL-collagen@PCL@PCL-gelatin three-layer small diameter artificial vascular grafts by electrospinning. (1st January 2023) - Lu, Xingjian; Zou, Hao; Liao, Xiaokun; Xiong, Yue; Hu, Xiaoyan; Cao, Jun; Pan, Jiaqi; Li, Chaorong; Zheng, Yingying
Abstract: The demand for artificial vascular grafts in clinical applications is increasing, and it is urgent to design a tissue-engineered vascular graft with good biocompatibility and sufficient mechanical strength. In this study, three-layer small diameter artificial vascular grafts were constructed by electrospinning. Polycaprolactone (PCL) and collagen (COL) were used as the inner layer to provide good biocompatibility and cell adhesion, the middle layer was PCL to improve the mechanical properties, and gelatin (GEL) and PCL were used to construct the outer layer for further improving the mechanical properties and biocompatibility of the vascular grafts in the human body environment. The electrospun artificial vascular graft had good biocompatibility and mechanical properties. Its longitudinal maximum stress reached 2.63 ± 0.12 MPa, which exceeded the maximum stress that many natural blood vessels could withstand. The fiber diameter of the vascular grafts was related to the proportion of components that made up the vascular grafts. In the inner structure of the vascular grafts, the hydrophilicity of the vascular grafts was enhanced by the addition of COL to the PCL, and human umbilical vein endothelial cells (HUVECs) adhered more easily to the vascular grafts. In particular, the cytocompatibility and proliferation of HUVECs on the scaffold with an inner structure PCL:COL = 2:1 was superior to other ratios of vascular grafts. The vascular grafts did not cause hemolysis of red blood cells. Thus, the bionic PCL-COL@PCL@PCL-GEL composite graft is a promising material for vascular tissue engineering.